PENGARUH ASIMETRI INFORMASI DAN MANAJEMEN LABA TERHADAP COST OF EQUITY CAPITAL PADAPERUSAHAAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - REIZKY IFONIE, REGINA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
This study aims to examine the effect of information asymmetry and earnings management cost of equity capital to real estate companies listed on the Stock Exchange. Objects in this study is the real estate company listed on the Stock Exchange and the study sample was obtained by 29 companies with research period is 2007-2009 financial year. Independent variables used are information asymmetry and earnings management, while the dependent variable is the cost of equity capital (COE). Methods of data analysis performed using multiple regression calculations to test the effect of independent variables on the dependent variable. Results from the study showed that together there is no significant effect between information asymmetry and earnings management with the cost of equity capital. This is because investors to assess at this time, issuers or companies issuing new common stock to cover debts is operational and investment, making the company less attractive to investors. In addition, investors consider other matters in investing in a company. The results of this study is consistent with research conducted by past research that states that two variables have a significant influence on the cost of equity capital.